Integration Of Science and Spirituality In Higher Education Based On Tarekat In Indonesia - Damanik, Agusman; Sitanggang, Cokro Malik; Sari, Winda (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The research problem is directly related to the model of tarekat-based HEI, because many unique relationships are found between HEI and tarekat, or vice versa tarekat and HEI. The efforts of spiritual ideologization practiced in educational institutions are efforts to expand the doctrine and ritual of tarekat through educational institutions. The results of this study identify the position of tarekat-based HEI such as UNPAB and IAILM, namely; that initially UNPAB was called the Metaphysics College then became the Panca Budi Development University (UNPAB), so that the position of the college is like a general college. While IAILM was initially an Islamic Da'wah College in its development into the Latifah Mubarokiyah Islamic Institute, where the position of the college is like an 'Islamic religious college based on Islamic Boarding Schools' by implementing a dormitory system as an effort to counter the development of science, especially religious science. The efforts of spiritual ideologization at UNPAB have more significant implications in influencing its students (students) than the spiritual ideologization that takes place at IAILM. This is because Habitus – spiritual teacher – IAILM historically has had a very large capital of honor and prestige in the community in Tasimalaya, so that its ideologization is only in the internal realm (Muslims).